Respuesta :
Step 1. Factor out the common term 2
n - 2 = 2(5n + 2)/2
Step 2. Cancel 2
n - 2 = 5n + 2
Step 3. Subtract n from both sides
-2 = 5n + 2 - n
Step 4. Simplify 5n + 2 - n to 4n + 2
-2 = 4n + 2
Step 5. Subtract 2 from both sides
-2 - 2 = 4n
Step 6. Simplify -2 - 2 to -4
-4 = 4n
Step 7. Divide both sides by 4
-1 = n
Step 8. Switch sides
n = -1
Answer:
n= -1
Step-by-step explanation:
n−2= 10n+4 /2
n+−2=5n+2(Distribute)
n−2=5n+2
Subtract 5n from both sides.
n−2−5n=5n+2−5n
−4n−2=2
Add 2 to both sides.
−4n−2+2=2+2
−4n=4
Divide both sides by -4.
−4n
−4
=
4
−4
n= -1